PENGARUH STRUKTUR AUDIT, KONFLIK PERAN, DAN KETIDAKJELASAN PERAN TERHADAP KINERJA AUDITOR - Fanani, Zaenal; Hanif, Rheni Afriana; Subroto, Bambang (Jurnal Akuntansi dan Keuangan Indonesia, 2008)
This research was aimed to examine and to obtain empirical evidence on audit structure, role conflict, and unclarity role toward auditor performance. This research was done in East Java. Retrieval o f sample was done by using proportionate stratified random sampling based on two strata (partner and audit staff). Data collecting was carried out with questionnaire submitted directly and by airmail. Number o f questionnaires distributed was 120 copies, but only 49 questionnaires returned (40,83%). Results show that audit structure and role conflict have significant effect on auditor performance, but unclarity role does not have significant effect on auditor performance.